2011
DOI: 10.5860/crl-74r1
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Library Impact on Student Persistence

Abstract: What impact does the academic library have on student persistence? This study explores the relationship between traditional library input and output measures of staff, collections, use, and services with fall-to-fall retention and six-year graduation rates at Association of Research Libraries member libraries. When controlling for race/ethnicity and socioeconomic status, a linear regression finds that a change in the ratio of library professional staff to students predicts a statistically significant positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 16 publications
0
58
1
Order By: Relevance
“…Another study, by Mark Emmons and Frances Wilkinson, compared the staff, collections, circulation, reference, and instruction of academic libraries with rates of retention and graduation at their parent institutions. 10 Emmons and Wilkinson's findings also point to a correlation between staffing and rates of retention and graduation. Gaby Haddow and Jayanthi Joseph built on this study with data from the ARL, IPEDS, and the National Center for Education Statistics (NCES) to analyze the relationship between student retention for one semester with checkouts, workstation use, and logins to library resources.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Another study, by Mark Emmons and Frances Wilkinson, compared the staff, collections, circulation, reference, and instruction of academic libraries with rates of retention and graduation at their parent institutions. 10 Emmons and Wilkinson's findings also point to a correlation between staffing and rates of retention and graduation. Gaby Haddow and Jayanthi Joseph built on this study with data from the ARL, IPEDS, and the National Center for Education Statistics (NCES) to analyze the relationship between student retention for one semester with checkouts, workstation use, and logins to library resources.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The University of New Mexico undertook a study that examined the impact academic libraries have on student persistence by focusing on the ratio of library professionals staff to students. 4 A study at Ryerson University notably found a .32-.34 increase in GPA among library users, with correlating trends in achievement for light and heavy users of library services. 5 The University of Minnesota examined library impact on retention and academic success of first year undergraduate students.…”
Section: March 2016mentioning
confidence: 99%
“…A variety of studies have attempted to do so (Breivik 1977;Knapp 1996;Hiscock 1986;Mallinckrodt and Sedlacek 1987;Lara 1981;Bean 2003;Rushing and Poole 2002). Early studies connected library use to retention (Kramer and Kramer 1968), but a more active paradigm now calls for librarians to make conscious efforts to increase their contact with students (Dow 1998, 280), especially individualized research assistance and personal attention (Bell, Keeping Them Enrolled 2008, 2;Mezick 2007, 565;Emmons and Wilkinson). Then librarians can conduct research that shows the impact of these interactions (Bell, Keeping Them Enrolled 2008, 4).…”
Section: Student Retention and Graduation Ratesmentioning
confidence: 99%